2004
DOI: 10.1073/pnas.0307145101
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking live flavivirus immunization with a noninfectious RNA vaccine

Abstract: Flaviviruses are human pathogens of world-wide medical importance. They have recently received much additional attention because of their spread to new regions (such as West Nile virus to North America), highlighting their potential as newly emerging disease agents. Using tick-borne encephalitis virus, we have developed and evaluated in mice a new genetic vaccine based on self-replicating but noninfectious RNA. This RNA contains all of the necessary genetic information for establishing its replication machiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
80
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 36 publications
4
80
0
4
Order By: Relevance
“…Hence, mRNA vaccines have been formulated with synthetic delivery vehicles such as liposomes (16) and cationic polymers (17) to increase potency. There are limited published data on the in vivo delivery of self-amplifying RNA using nonviral delivery strategies (3,14,18), and none has taken advantage of the recently developed, clinically suitable delivery systems for siRNA (19,20). There has been extensive work on viral delivery of self-amplifying RNA using viral replicon particles (VRPs) (4,11,(21)(22)(23)(24).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, mRNA vaccines have been formulated with synthetic delivery vehicles such as liposomes (16) and cationic polymers (17) to increase potency. There are limited published data on the in vivo delivery of self-amplifying RNA using nonviral delivery strategies (3,14,18), and none has taken advantage of the recently developed, clinically suitable delivery systems for siRNA (19,20). There has been extensive work on viral delivery of self-amplifying RNA using viral replicon particles (VRPs) (4,11,(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Although plasmid DNA (pDNA) vaccines have proven to be a flexible platform and are broadly effective in small animal models, they have generally lacked potency in human clinical trials (2). Recombinant viral vector technologies have the advantage of efficient delivery of the nucleic acid payload, but their utility is often hampered by antivector immunity, production limitations, and safety concerns (3,4). In 1990, Wolff et al (5) demonstrated that direct injection ("naked delivery") of messenger RNA (mRNA) or pDNA into the skeletal muscle of a mouse resulted in expression of the encoded protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, replicons were described for several flaviviruses including DENV-2 (Ng et al 2007), DENV-3 (Mosimann et al 2010), YFV (Jones et al 2005), WNV and TBEV (Kofler et al 2004).…”
mentioning
confidence: 99%